A Study on Instructional Supervision by Principals in Type 2 and Type 3 Schools in Sri Lanka - Kumari, H.M.L. (National Education Research and Evaluation Centre, 2022)
The main purpose of this study was to examine how principals engage in instructional supervision in Type 2 and Type 3 schools in Sri Lanka. Three research questions were used to guide the study to a rational conclusion. Mixed-method approach was adopted in the study to triangulate data. A questionnaire and semi-structured interview schedules were used to obtain data from 150 teachers, 10 principals and 10 section heads in 10 selected Type 2 and Type 3 schools using the simple random sampling techniques. Tables, percentages and graphs were used to analyze quantitative data and the qualitative data were analyzed using thematic analysis in order to address the research questions. The findings revealed that all principals in Type 2 and Type 3 schools have positive perceptions about the role of instructional supervision and have formed an instructional supervisory team including the principal in their schools. However, the study revealed that the majority of principals in Type 2 and Type 3 schools do not engage in instructional supervision on account of major administrative duties forced upon them. The study further revealed that the existing internal supervisory team, which engages in instructional supervision, does not conduct post observational discussions which help teachers to identify their strengths and the areas that need further improvement. It is, therefore, recommended that the principals need to carry out adequate instructional supervision of teachers to improve their teaching skills and professional development
Keywords: Instructional supervision; Internal supervision; Professional development